2000
DOI: 10.1103/physrevb.62.6577
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of YVO3 single crystals

Abstract: The magnetic properties of YVO 3 single crystals have been studied in the temperature range from 350 to 4.2 K and in magnetic fields up to 7 T. It is found that in an applied field less than 4 kOe remarkable magnetization reversals occur at two distinct temperatures: an abrupt switch at T s ϭ77 K associated with a first-order structure phase transition and a gradual reversal at T*Ϸ95 K without a structural anomaly. Most interestingly, the magnetization always switches to the opposite direction if the crystal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
163
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(175 citation statements)
references
References 17 publications
10
163
1
Order By: Relevance
“…During past decades, several groups have reported similar anomalous diamagnetism caused by a reversal of the ferromagnetic component of a canted antiferromagnet and this unusual phenomenon is named reversal magnetization, which indicates that the direction of the magnetization is the reverse of that of the applied magnetic field below the compensation temperature (9-13). Recently, Ren et al (14) have been found reversal magnetization in single crystals of YVO 3 . The mechanism to explain this phenomenon is related to the competition of the single V 3+ magnetic anisotropy and the antisymmetric Dzialoshinsky-Moriya interaction.…”
Section: Resultsmentioning
confidence: 99%
“…During past decades, several groups have reported similar anomalous diamagnetism caused by a reversal of the ferromagnetic component of a canted antiferromagnet and this unusual phenomenon is named reversal magnetization, which indicates that the direction of the magnetization is the reverse of that of the applied magnetic field below the compensation temperature (9-13). Recently, Ren et al (14) have been found reversal magnetization in single crystals of YVO 3 . The mechanism to explain this phenomenon is related to the competition of the single V 3+ magnetic anisotropy and the antisymmetric Dzialoshinsky-Moriya interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The anisotropic interactions are known to play a crucial role in the weak ferromagnetism in α-Fe 2 O 3 [7,8] and RFeO 3 (R = rare-earth) [9,10], the strong magnetoelectric effect in multiferroic materials such as TbMnO 3 [11,12], the reversal magnetization in YVO 3 [13] and the electron spin resonance (ESR) behavior in KCuF 3 [14].…”
Section: Introductionmentioning
confidence: 99%
“…An inverse situation with respect to manganites and cuprates, with AF interactions within (a, b) planes coexisting with FM superexchange along the c-axis, is encountered in the so-called C-AF phase, observed in cubic vanadates: in LaVO 3 below the Néel temperature T N ≃ 143 K, 12 and in YVO 3 at intermediate temperatures 77 < T < 116 K. 13 Finally, G-type AF order, with cubic symmetry and the magnetic order parameter staggered in all three directions, is found in CaMnO 3 , LaTiO 3 , and also in the low-temperature phase of YVO 3 .…”
mentioning
confidence: 99%